2007
DOI: 10.5694/j.1326-5377.2007.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behaviours of young Indigenous people in Townsville concerning relationships, sex and contraception: the “U Mob Yarn Up” project

Abstract: Objective: To gain some understanding of the attitudes and behaviours of Indigenous young people in Townsville concerning relationships, contraception and safe sex. Design: Cross‐sectional study using a computer‐assisted self‐administered survey and single‐sex focus group discussions designed by a Young Mums’ Group operating on participatory action principles and acting as peer interviewers. Participants and setting: 171 Indigenous students in Years 9–11 at three high schools and 15 residents of a homeless you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 21 publications
1
55
1
1
Order By: Relevance
“…Many Aboriginal and/or Torres Strait Islander women have cultural beliefs regarding gender roles and participation during the maternity period and have reported feelings of ‘shame’ in being cared for in birth by men [15] and when discussing reproductive health issues in general [49]. Therefore, not having a choice in the gender of caregivers could cause distress for some Aboriginal and/or Torres Strait Islander women.…”
Section: Discussionmentioning
confidence: 99%
“…Many Aboriginal and/or Torres Strait Islander women have cultural beliefs regarding gender roles and participation during the maternity period and have reported feelings of ‘shame’ in being cared for in birth by men [15] and when discussing reproductive health issues in general [49]. Therefore, not having a choice in the gender of caregivers could cause distress for some Aboriginal and/or Torres Strait Islander women.…”
Section: Discussionmentioning
confidence: 99%
“…Despite providing free access to contraception, the UK still has one of the highest rates of teen pregnancies in the world [16]. Given that the study population was already “accessing” a family planning service, this reported “lack of access” may reflect other variables - embarrassment in purchasing or discussing contraception; fear of carrying of condoms being seen as a premeditation of sex; inability to anticipate sex especially in the context of alcohol [17]; fear of lack of confidentiality [18]; transport problems, difficulties of getting time off work/school, taking too long to get an appointment or even waiting times in clinics [19]. “Accessability to contraception” certainly was seen to be an issue in adolescent populations [19] but it still remains unclear why this is so.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the skew towards the younger cohort, our study was not powered to detect a difference for women aged more than 40 years old. The literature suggests that for those less than 25 years old, this increased vulnerability may be due to higher fertility, shorter intervals between sex [20], having multiple partners [21], and/or less capacity to anticipate sex (especially in the context of alcohol) [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies from other countries showed that unintentional pregnancies among the young could also be due to lack of power to negotiate with their partners on whether contraceptives should be used [24][25]. In contrast, coercion and lack of power in negotiating contraceptive use were not raised in our FGDs.…”
Section: Discussionmentioning
confidence: 73%
“…Prior studies noted that unintentional pregnancies among the young were due to misinformation and ignorance of sexual issues [24][25]. It was found that girls in secondary schools bear the greatest risks of unexpected consequences from sexual activity as most engaged in sexual intercourse without possessing adequate information about human reproduction and contraception [26].…”
Section: Discussionmentioning
confidence: 99%